Voice recognition system for controlling electrical appliances in smart hospital room - Agustin, Eva Inaiyah; Yunardi, Riky Tri; Firdaus, Aji Akbar (Telkomnika, 2019)
Because the existing appliances are controlled by manual switch [11] such as bed, lighting, medical aid button, etc. [...]communication only point-to-point with the position of the transmitter and the receiver must be in a line-of-sight (LoS). [...]the angle of transmission only 0°C and the distance of transmission is short [21]. [...]if there are 12 commands, then the loading process is done alternately for each subject. Age and gender factors strongly influence the dominant frequency of voice signals. [...]the authors re-record the new training data containing all subject sounds.